Focus Assoc. Prof. Dr. Muhammad Hussain Ismail - UiTM, Korporat UiTM
Focus Assoc. Prof. Dr. Muhammad Hussain Ismail from Faculti of Mechanical Engineering, whose research area in porous NiTi and metal injection moulding has led to innovation on bone-replacement material.